Transcatheter Aortic Valve Implantation: All Transfemoral? Update on Peripheral Vascular Access and Closure - Perrin, Nils; Bonnet, Guillaume; Leroux, Lionel; Ibrahim, Réda; Modine, Thomas; Ben Ali, Walid (Frontiers in Cardiovascular Medicine, 2021)
Transfemoral access remains the most widely used peripheral vascular approach for transcatheter aortic valve implantation (TAVI). Despite technical improvement and reduction in delivery sheath diameters of all TAVI platforms, 10-20% of patients remain not eligible to transfemoral TAVI due to peripheral artery disease. In this review, we aim at presenting an update of recent data concerning transfemoral access and percutaneous closure devices. Moreover, we will review peripheral non-transfemoral alternative as well as caval-aortic accesses and discuss the important features to assess with pre-procedural imaging modalities before TAVI.